2006
DOI: 10.1093/molbev/msk011
|View full text |Cite
|
Sign up to set email alerts
|

A Sex-Specific Marker Reveals Male Heterogamety in European Tree Frogs

Abstract: Most amphibians examined so far show undifferentiated sex chromosomes. The heterogametic sex's identity, usually revealed through indirect means, often varies among closely related species or even populations (as do sex-linkage groups), suggesting great evolutionary instability of the sex-determining genes. Here we take advantage of a sex-specific marker that amplifies in several related species of European tree frogs (Hyla arborea group) to disclose a homogeneous pattern of male heterogamety. Besides relevanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…More than 200 Million years of divergence between Pipidae, Bufonidae and Hylidae, and about 100 My between the latter two anuran families (www.timetree.org), have led to the evolution of profound differences in genome size and composition with ecotoxicological relevance (Helbing, 2012), various life history and ecologies including larval feeding (Avila and Frye, 1978;Degani, 1986;Schneider and Grosse, 2009;St€ ock et al, 2009), as well as physiology (Wilbur, 1980) and sex determination pathways (e.g. Berset-Br€ andli et al, 2006;St€ ock et al, 2011aSt€ ock et al, , 2011bTamschick et al, 2015;Yoshimoto et al, 2008). Not surprisingly, these complex differences appear to cause susceptibility differences to endocrine disruption (cf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 200 Million years of divergence between Pipidae, Bufonidae and Hylidae, and about 100 My between the latter two anuran families (www.timetree.org), have led to the evolution of profound differences in genome size and composition with ecotoxicological relevance (Helbing, 2012), various life history and ecologies including larval feeding (Avila and Frye, 1978;Degani, 1986;Schneider and Grosse, 2009;St€ ock et al, 2009), as well as physiology (Wilbur, 1980) and sex determination pathways (e.g. Berset-Br€ andli et al, 2006;St€ ock et al, 2011aSt€ ock et al, , 2011bTamschick et al, 2015;Yoshimoto et al, 2008). Not surprisingly, these complex differences appear to cause susceptibility differences to endocrine disruption (cf.…”
Section: Discussionmentioning
confidence: 99%
“…These ecological differences might cause variance in EDC-exposure, especially between ground-feeding and filterfeeding larvae. Importantly, these species also differ in their sex determination systems with either male heterogamety (XX/XY) in H. arborea (Berset-Br€ andli et al, 2006;St€ ock et al, 2011aSt€ ock et al, , 2011b and B. viridis (St€ ock et al, 2011a;Tamschick et al, 2015) or female heterogamety (ZZ/ZW) in X. laevis (Chang and Witschi, 1956;Yoshimoto et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Screening populations from Western Switzerland with the Ha5-22 primers (Arens et al 2000) showed allele 230 to be fixed on the proto-X, while allele 236 was fixed on the proto-Y (Berset-Brändli et al 2006;. Sequencing both alleles allowed identifying three frame-preserving indels (eight amino acids in total) within the central glutamine-rich (poly-Q) region, with no sign of decay in the Y copy.…”
Section: Introductionmentioning
confidence: 99%
“…Nothing is known about amphibian master sex-determination genes and very little about sex-chromosome evolution (Schartl 2004). The European tree frog Hyla arborea has homomorphic sex chromosomes (Anderson 1991), but male heterogamety was recently revealed by the sex-specific patterns of a microsatellite-like marker (Berset-Brändli et al 2006. At locus Ha5-22, all females investigated were homozygous for allele 235 and all males were heterozygous for alleles 235/241, pointing to a location within the nonrecombining region of nascent sex chromosomes, with allele 235 fixed on the proto X and 241 on the proto Y.…”
mentioning
confidence: 99%
“…The successful amplification of Ha5-22 in several hylid species (Berset-Brändli et al 2006) as well as the nature of its tandem repeat (a trinucleotide CAG repeat) suggested a location within the coding region of a conserved gene. To address this point, we analyzed the mRNA expression of Ha5-22 in H. arborea embryos at different developmental stages by cDNA reverse transcription (Methods in supplemental material).…”
mentioning
confidence: 99%